Localized intrahepatic IgG4-related sclerosing cholangitis (IgG4-SC) as an additional type of IgG4-SC: a systematic analysis of 12 cases. (4th March 2018) - Mo, Zhichao; Ramen, Kuvaneshan; Shan, Yunfeng; Zhou, Mengtao; Zheng, Xiangwu; Wu, Xiuling; Yu, Zhengping; Ji, Xiaoke; Zhang, Qiyu; Zeng, Qiqiang
Abstract: Objectives: IgG4-related sclerosing cholangitis (IgG4-SC), a recently defined disease entity, has been classified into four types based on the stricture regions revealed by cholangiography. However, localized intrahepatic IgG4-SC is not included into the classification. This study aimed to analyze and characterize localized intrahepatic IgG4-SC and justify the inclusion of this type into the classification. Methods: PubMed and Embase were searched for studies published from March 2001 to June 2017 reporting localized intrahepatic IgG4-SC. Data were obtained and analyzed from the included articles. Results: Twelve cases of localized intrahepatic IgG4-SC were included. All patients were adults with the median age of 73 years (range 46–78), and had a male preponderance (88.9%). The most common clinical presentation was obstructive jaundice (50%), abdominal pain (25%) and absence of symptoms (25%). On imaging and macroscopically, localized intrahepatic IgG4-SC presented with three subtypes, i.e., mass-forming ( n  = 6, 50%), stricture ( n  = 5, 41.7%) and periductal infiltrating ( n  = 1, 8.3%) subtypes. Among the eight cases with diagnoses reported, six patients were misdiagnosed as intrahepatic cholangiocarcinoma; one was diagnosed as hepatic mass and one as IgG4-SC before biopsy or operation. Information on treatment was available on 10 cases; eight underwent surgical resection, one received steroid treatment alone and one underwent endoscopic biliary drainage. No relapse was noted in patients with surgical resection during a period of followed up. Conclusions: The localized intrahepatic IgG4-SC presents with mass-forming, stricture and periductal infiltrating subtypes, and should be recognized as an additional type of IgG4-SC according to the cholangiographic classification or anatomic site.